Optimized multiplex PCR-NGS for comprehensive HLA genotyping in Chinese populations: resolving ambiguities at high resolution - Haider, Cuello Garcia; Sun, Binbin; Wang, Yinfeng; Zhang, Zhoufan; Cao, Changling; Zhu, Yiying; Abdelhak, Ouzaouit; Huang, Huiqiang; Liu, Haitao; Jiang, Tingya; Dong, Xueping; Zhou, Yang; et al. (Frontiers in Immunology, 2025)
IntroductionAccurate human leukocyte antigen (HLA) genotyping is critical for organ transplantation to ensure donor-recipient compatibility. Conventional methods, such as sequence-based typing (SBT), often face challenges in resolving allelic ambiguities, particularly in highly polymorphic regions of HLA loci. Therefore, this study aimed to develop 6 locus multiplex primers combined with Next-generation sequencing NGS for high-resolution of long sequenceshigh-resolution sequencing, focusing on improving sequencing depth and reducing costs.MethodsMultiplex PCR primers targeting HLA-A, -B, -C, -DPB1, -DQB1, -DRB1 loci were designed using high-frequency alleles from public databases. PThe primers were optimized using as reference the sequencing depth across loci. The method was validated using SBT and probe capture‑based targeted next‑generation sequencing to evaluate its approach accuracy. Moreover, 770 samples from Chinese population were further studied to verify the allele frequency adding information about HLA types of this population.ResultsThe optimized multiplex PCR-NGS sequencing showed depths within athe target range of 100-1000 with high accuracy determined in the 2ndtwo-digit ,and 4thfour-digit and six-digit HLA typing, with a reliability of ≥ 98%, ≥ 95% and ≥ 95% respectively in both methods.DiscussionAllele digits in the HLA-class I and II loci. However, in the 6th digit of HLA-C, -DQB1, and -DRB1 the accuracy was 94.74%. The developed multiplex PCR-NGS method offers a reliable, cost-effective approach for high-resolution HLA genotyping, and may be particularly suitable for clinical studies, especially in donor-recipient matching during organ transplantation.